Isobaric analogue resonances in proton elastic and inelastic scattering - Bund, G. W.; Blair, J. S. (Elsevier, 1970)
A model for proton elastic and inelastic scattering at isobaric analogue resonances in the one level approximation is presented. The basic assumptions made are that the coupling of the open channels to compound nuclear states with isobaric spin T0- 1 2 is simulated by a phenomenological complex potential acting in the entrance and exit channels and that internal mixing of the isobaric analogue state with complicated compound nuclear states is small. The fractional parentage expansions characteristic of (d, p) stripping reactions on the parent states are explicitly introduced. The elastic and inelastic partial widths and the total width for the analogue of the ground state of 208Pb are studied for different optical potentials and partial agreement with experiment is obtained. © 1970.